(untitled) (Malaysian Management Journal, 2020)
Prior studies have revealed that foreign shareholders have a greater influence on dividend policy. However, it is unclear how foreign owners in large firms affect the propensity to pay dividends. This paper is aimed at exploring the relationship between the propensity to pay dividends and foreign ownership. It also examined the moderating role of firm size on the relationship between the decision to pay cash dividend and foreign ownership. The study uses pooled logistic regression on a data set of non-financial listed firms on the Nigerian Stock Market from 2011 to 2015. The results showed that foreign ownership has a great tendency to influence the propensity of a firm to pay a cash dividend. The effect is more pronounced in larger firms, thus, indicating that in larger firms, foreign owners mitigate agency problems using dividends. Based on the findings, firms should be encouraged to pay a dividend to attract foreign investors and in return will help the firms to acquire the expertise of foreign owners.